Investigation of the morphofunctional status of macrophages in abdominal adhesions in rats and on exposure to oxidized dextran - M. A. Karpov; A. P. Nadeev; V. A. Shkurupiy; N. P. Bgatova; A. V. Basova; M. A. Volchek; A. V. Volchek (Сибирский научный медицинский журнал, 2025)
Abdominal adhesions result from the organization of fibrinous exudate and subsequent fibrosis, attributed to the low phagocytic activity of macrophages associated with their M1 phenotype. Oxidized dextran (OD) can limit the development of fibrosis by exerting a stimulating effect on phagocytosis.The aim of the study is to investigate the morphofunctional status of macrophages during the formation of abdominal adhesions in an experimental model and under exposure to OD.Material and methods. In male Wistar rats (n = 30), the adhesive process in the abdominal cavity was simulated. The animals were divided into 3 groups: group 1 – control, with adhesions in the abdominal cavity; group 2 rats were injected once with 2 ml of OD 5 % aqueous solution; the 3rd group consisted of intact animals. The rats were removed from the experiment on the 7th and 21st days. Histological immunohistochemical (Il-10, IFNγ, Il-1, TNFα, TGF-β) and electron microscopic study of abdominal adhesions, morphometry of structures were performed.Results and discussion. Macrophages in adhesions of group 1 and 2 rats were larger, compared to those in intact animals. On days 7 and 21 macrophages in group 2 rats were 19 % and 2.5 times larger, respectively, compared to group 1 animals, contained in the cytoplasm a greater number of phagosomes, phagolysosomes and rough endoplasmic reticulum, by the 21st day nuclear-to-cytoplasmic ratio was shifted towards the cytoplasm. The expression of IFNγ in the infiltrates of adhesions in group 2 rats increased 3,2-fold, indicating greater phagocytotic activity of macrophages. The expression of IL-10 and TGFβ on the 7th and 21st days was represented in a larger number of macrophages of group 2 than group 1 rats (2.7 and 4.1 times, respectively), but IL-1 and TNFα ‒ in a smaller number (4.6 and 3.2 times, respectively), which corresponded to the phenotypic characteristics of M2 macrophages.Conclusions. The population of macrophages in inflammatory infiltrates of abdominal adhesions is heterogeneous, there are signs of M1 and M2 type. Under the influence of OD, the phagocytic activity of M2 type macrophages increases, preventing the formation of adhesions.